Microsoft Expression Web 4 : LiveLessons - Rand-Hendriksen, Morten (LiveLessons (Indianapolis, Ind.), 2010)
"These practical videos walk you through starting projects, building effective pages, using Code View, and thoroughly mastering Expression Web 4's powerful CSS capabilities. You'll find hands-on coverage of Dynamic Web Templates and site management, browser testing with SuperPreview, search engine optimization with the new SEO Checker, and much more!"--Resource description page.